2010
DOI: 10.1002/cncr.24879
|View full text |Cite
|
Sign up to set email alerts
|

Fyn

Abstract: Fyn is 59-kDa member of the Src family of kinases that is historically associated with T-cell and neuronal signaling in development and normal cellular physiology. Whereas Src has been heavily studied in cancer, less attention has been traditionally awarded to the other Src kinases such as Fyn. Our group has shown that Fyn is particularly upregulated in prostate cancer in contrast to the alternative members of the Src family. This suggests that it may mediate several important processes attributed to Src kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(105 citation statements)
references
References 46 publications
0
105
0
Order By: Relevance
“…Moreover, FYN is a Proto-oncogene tyrosine-protein kinase of the Src family of kinases, typically associated with T-cell and neuronal signaling in development and normal cell physiology. Disruptions FYN signaling pathways often have implications in the formation of a variety of cancers (Saito et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, FYN is a Proto-oncogene tyrosine-protein kinase of the Src family of kinases, typically associated with T-cell and neuronal signaling in development and normal cell physiology. Disruptions FYN signaling pathways often have implications in the formation of a variety of cancers (Saito et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that it is involved in the regulation of T-cell development and activation, factor and cytokine receptor signaling, cell–cell adhesion, integrin-mediated signaling, ion channel function, platelet activation, T- and B-cell receptor signaling, axon guidance, mitosis, differentiation of NK cells (Palacios and Weiss, 2004; Salmond et al, 2009; Saito et al, 2010). …”
Section: Introdutionmentioning
confidence: 99%
“…Fyn is up-regulated in prostate cancer where it exhibits tumorigenic potential in processes of cellular motility. Its interaction with several signal molecules, including focal adhesion kinase (FAK), Akt and paxillin, that play an essential role in prostate cancer progression, might account for the described cell transformations and possibly lends credence to its role in both cancer progression and metastasis [10-12]. …”
Section: Introductionmentioning
confidence: 99%